The values of Hellenic culture as the foundation of Nietzsche’s philosophy - Stanković Pejnović, Vesna (Serbian political thought, 2023)
The paper is examining Nietzsche’s attempt to fuse his studies of antiquity with his critique of modernity. For Nietzsche, modernity is in a state of crisis. If we look at the intellectual relationship early Nietzsche develops with the Greek philosophers, it can be discovered the guiding problems motivating a good deal of Nietzsche’s later work, but also and problem-solving strategies that marks the development of his whole philosophical journey. The aim of the work is to prove that the foundation of Nietzsche’s philosophy is found in the value system of the ancient Greeks, while the central problem is culture, which he interprets through the prism of Greek cultural values ​​that reconcile thinking, desire and the will to live with the will to power. Nietzsche claims that the Greeks have offered humanity exemplary models of cultural and individual development. ’Heterogeneous’ prePlatonic philosopher is essential to the homogeneity of Greek culture. Nietzsche’s classicism amounts is criticism of his own times, but in the time is the base of his whole philosophical opuses. Nietzsche insists, modern Europe could not simply ’imitate the Greeks’. As individuals, the Greeks were psychologically healthier than the moderns were; they were emotionally stronger, in Nietzsche’s view, more self-assured, less alienated from their own natures and from nature as such. They enjoyed these advantages because the common culture uniting the Greek world was stronger and more clearly defined, and this strength helped the Greeks find reliable answers to questions concerning the purpose of their being in the world. They knew, instinctually, why they existed, and in their various philosophies and tragic festivals, each of them affirmed to himself the meaning of his own particular existence, and by confirming the basic assumptions and worth of the culture’s institutions, each of them affirmed the meaning of existence as such. The most significant problems and concepts arising in Nietzsche’s philosophy developed through his engagement with Greek culture and thought and for these reason, studies of Nietzsche failing to take into account these problems and concepts from their origins run the risk of misconceiving Nietzsche’s ideas by a considerable margin. Nietzsche does not reject not tradition or modernity’s inheritance of it. In Nietzsche’s reading, Greek culture, like all flourishing types, understood the need for meaning, purpose, direction and goals, and responded to this need by ’toppling boundary stones’, but also by constructing ’new religions and moralities’. Both responses are the function of such artistic, philosophical visions affected as they were in the age of Greek tragedy. Will to power serves him as a tool for understanding the conventional paths of modern skepticism and pessimism. Nietzsche’s notion of self-overcoming contains the meaning of maturity and spiritual growth, based on the ancient will to life. The key to the meaning of the will to power is Nietzsche’s notion of self-overcoming after achieving maturity and power. The optimal will to power is realized in the ideal Übermensch based on the ancient hero.